What will the OECD BEPS indicators indicate? - Jost H. Heckemeyer; Katharina Nicolay; Christoph Spengel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
As part of its action plan against base erosion and profit shifting (BEPS), the OECD (2015) has proposed six indicators to measure profit shifting activity. These indicators add to past and ongoing efforts in academic tax research to empirically identify the scale and tax sensitivity of international profit shifting. In this paper, they discuss whether the proposed OECD indicators indeed represent methodological advances and critically assess their informative value. While a certain need for "easy-access" indicators to measure the relevance of the base erosion problem seems justified, their discussion reveals that the indicators come up with certain shortcomings, many of them acknowledged by the OECD (2015) itself, that prevent them from reliably tracing profit shifting activity in available international data. With one notable exception, the OECD's indicators lack consistent counterfactuals and comparison groups which are essential benchmarks for the observed data. Even the most promising approaches require representative and timely data that covers firms' global activity, including tax haven operations. With better access to such high-quality micro-level data, it will be more promising to empirically isolate the effects of profit shifting from relocations of real economic activity and value creation.
Keywords: H20; H25; H26; 330; Tax policy; International Taxation; BEPS; OECD; Base Erosion and Profit Shifting